Australian trade policy 1942-1966 : a documentary history - Crawford, John Grenfell; Anderson, Nancy; Morris, Margery G. N. (Canberra : Australian National University Press , Toronto : University of Toronto Press, 1968)
This book gives an account of the development of Australian trade policy since World War II and of change in the international and domestic framework within which it has been conducted.
Includes index.
Includes bibliographical references: p. 621-629
ijb 14/01/2019
Loans
Keywords: International trade; Commercial policy; Commerce; Foreign trade regulation; Australia